Quality management in MSIS - Marotta, Adriana (2003)
This paper presents our first incursion in the problem of quality management in Multi-Source Information System (MSIS). We state the problem and experiment with the definition and classification of quality properties. We also experiment with a solution for the problem of quality evaluation in a MSIS considering a few selected properties.